1974
DOI: 10.1017/s0022029900014862
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary proteins on rennin and pepsin content of preruminant calf vell

Abstract: Studies were undertaken to determine the influence of dietary proteins on the rennin and pepsin contents of preruminant calf veil. Three groups of 12 Friesian calves were each fed either milk proteins, whey proteins or a 50:50 mixture of these 2 diets. They were slaughtered at a constant weight of 150 kg and their veils collected and dried. Another group of veils was obtained from 8 animals that had been fed milk proteins in a separate experiment. The extraction of the abomasal enzymes was carried out at acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

1975
1975
2018
2018

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 5 publications
0
5
1
1
Order By: Relevance
“…Assuming that 50 % of the total MCA of the tissue was extracted in each case, the enzymic activities of the crude extracts showed that total units/g tissue were considerably higher for the lamb and kid than for the cow, sheep and goat, which were fairly similar ( Table 1). The levels of enzymic activity/g tissue for all sources in this study were considerably lower than that reported for calf chymosin by Garnot et al (1974). The enzymic activity in piglet stomach was very much lower (4 RU/g) than that in the other sources and this together with the small size of piglet stomachs resulted in greater difficulty in isolating piglet chymosin.…”
Section: Enzyme Isolationcontrasting
confidence: 75%
“…Assuming that 50 % of the total MCA of the tissue was extracted in each case, the enzymic activities of the crude extracts showed that total units/g tissue were considerably higher for the lamb and kid than for the cow, sheep and goat, which were fairly similar ( Table 1). The levels of enzymic activity/g tissue for all sources in this study were considerably lower than that reported for calf chymosin by Garnot et al (1974). The enzymic activity in piglet stomach was very much lower (4 RU/g) than that in the other sources and this together with the small size of piglet stomachs resulted in greater difficulty in isolating piglet chymosin.…”
Section: Enzyme Isolationcontrasting
confidence: 75%
“…In fact, casein in the milk is the main factor causing the secretion of prochymosin. It has been shown (Garnot 1974) that the abomasums of calves fed a casein diet contained more chymosin and stable levels of pepsin, and the higher the content of casein in the diet, the longer the retaining time of chymosin and pepsin in the abomasums. This could stimulate the secretion amount and speed of prochymosin by cells of the fundus gland of abomasums.…”
Section: Discussionmentioning
confidence: 99%
“…Ce sont des procédés basés sur une macération des caillettes, séchées ou fraîches, en milieu acide, généralement dans des solutions d'acide chlorhydrique [3][4][5][6][7]. Dans ces procédés l'extraction et l'activation des pro-enzymes se font simultanément, de sorte que l'obtention des enzymes actives est plus rapide en général que dans le procédé traditionnel.…”
Section: La Préparation D'extraits Coagulants à Partir De Caillettes Deunclassified